Physical work demands, hypertension status, and risk of ischemic heart disease and all-cause mortality in the Copenhagen Male Study - Andreas Holtermann; Ole Steen Mortensen; Hermann Burr; Karen Søgaard; Finn Gyntelberg; Poul Suadicani (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVE: Increased risk of ischemic heart disease (IHD) mortality from high physical work demands has been observed among men with low physical fitness and leisure time physical activity. We tested whether hypertensive men are at a particularly high risk of IHD mortality when exposed to high physical work demands. METHOD: We carried out a 30-year follow-up of the Copenhagen Male Study of 5249 gainfully employed men aged 40-59 years. Of these, 274 men with a history of myocardial infarction or prevalent symptoms of angina pectoris or intermittent claudication were excluded from the follow-up. Men were classified as having hypertension when any of the following factors was present: (i) treatment for hypertension, (ii) a systolic blood pressure of >160 mm Hg, or (iii) a diastolic blood pressure of >90 mm Hg. Physical work demands were determined by two self-reported questions. RESULTS: Of the eligible study population, 587 men (11.9%) died due to IHD. Hypertensive men had more than a doubled risk of IHD mortality [hazard ratio (HR) 2.16, 95% confidence interval (95% CI) 1.80-2.59]. Cox analyses - adjusted for age, smoking, alcohol, body mass index, diabetes, physical fitness, leisure time physical activity, and social class - showed that high physical work demands were associated with an increased risk of IHD and all-cause mortality among normotensive men (N=4127, HR 1.36, 95% CI 0.96-1.92 and HR 1.24, 95% CI 1.06-1.44, respectively), but not among the hypertensive men (N=808, HR 1.07, 95% CI 0.63-1.81 and HR 1.07, 95% CI 0.80-1.42, respectively) using men with low physical work demands as the reference. CONCLUSION: Compared to normotensive men, hypertensive men did not have a higher risk of IHD or all-cause mortality from high physical work demands.